Rancang Bangun Sistem Informasi Administrasi Publik Berbasis Website di Desa Cileles Kecamatan Jatinangor - Marwin, Marwin; Rohmato, Ricky (Jurnal Dimamu, 2024)
The design of a website-based public administration service information system is a system for solving problems in the administration section in Cileles Village. The design of this website-based administrative service information system uses the Rapid Application Development development method with stages with the Joint requirement planning (JRP) technique, Joint application design (JAD) technique, information system construction and transition. The research method used is descriptive method, to obtain data using the method of observation, interviews and literature study. This website is implemented using the PHP (Hypertext Preprocessor) programming language and uses the Laragon application to connect to the MYSQL database. The results of the study show that website-based public administration services in Cileles Village can improve people's welfare in the process of making public administration services more effective and efficient.